Atividade antifúngica de fragmentos peptídicos derivados da Crotalicidina frente a Candida spp - Cruz, Gabriela Silva (2023)
Crotalicidin (Ctn), an antimicrobial peptide related to cathelicidin from the venom gland of the South American rattlesnake Crotalus durissus terrificus, as well as C-terminal fragment, Ctn[15-34], have demonstrated important activities against microorganisms such as bacteria, yeast and trypanosomatid protozoa and certain tumor cell lines. Recently, the fragmente RhoB-Ctn[1-9] demonstrated antimicrobial action against yeasts and bacteria. To improve its antifungal activity, instead Rhodamine B, tetradecanoic acid (myristic acid) was added to this structure, in covalent bond with the N-terminal portion of the peptide, being nicknamed Myr-Ctn[1-9]. Yeasts of the genus Candida have particularities depending on the species and origin of the isolates, such as the ability to produce virulence factors, which contribute to pathogenicity and resistance to traditional medicines, making it necessary to identify new alternatives for antifungal agents. Given the above, this study aimed to expand the investigation into the spectrum of antifungal activity of peptide fragments Myr-Ctn[1-9] and Ctn[15-34] derived from Crotalicidin, against strains of Candida spp. This is an analytical study, with a quantitative approach, using 35 strains of Candida sp., collected from the oral microbiota of healthy individuals. Clinical isolates of Candida spp. from different types of clinical specimens such as blood, urine, bronchoalveolar lavage, tracheal aspirate and nail scrapings were also used for testing. Before the sensitivity tests with the peptides, a survey was carried out on the sensitivity profile of conventional antifungal agents and the production of virulence factors (hemolytic activity and phospholipase). Finally, the activity of Ctn[15-34] on Candida albicans biofilm was evaluated. Sensitivity tests were performed with 25 strains of Candida spp. and it was found that the distribution of Minimum Inhibitory Concentration (MIC) values obtained varied between groups of different species (p-value = 0.04), with median inhibitory peptide concentrations lower for non-albicans Candida strains. Myr-Ctn[1-9] showed lower MIC values for all strains compared to Ctn[15-34] with a range from 0.313 to 1.25 μM (p value < 0.01). Ctn[15-34] inhibited biofilm formation (50%) by a standard strain of Candida albicans at a concentration of 75 μM. Overall, Myr-Ctn[1-9] and Ctn[15-34] are potential antifungal derivatives that exhibit activities against Candida spp., demonstrating that Crotalicidin-derived peptides are promising models for further studies aimed at the ultimate goal of development of new antifungals.